Determinants of TikTok Live Commerce Purchase Intention: Service Quality, Price, Trust, Customer Review, And Free Shipping - Aji Priambodo (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
Consumers now favor live commerce greatly, especially those in the younger age group because it offers a direct interaction experience between sellers and customers. The purpose of this study is to analyze the influence of service quality, price, trust, customer reviews, and free shipping on purchase intention in TikTok Live Commerce among students at Institut Teknologi dan Bisnis Muhammadiyah Purbalingga. The population in this study was all students of the Muhammadiyah Purbalingga Institute of Technology and Business, totaling 73 people. The data collection method used in this research is a direct field survey, which involves sampling from a single population using a questionnaire as the main data collection instrument for explanatory purposes. The research findings indicate that service quality has a positive and significant influence on purchase decisions; price has a positive and significant influence on purchase decisions; trust has a positive and significant influence on purchase decisions; customer reviews have no significant influence on purchase decisions; and free shipping has a positive and significant influence on purchase decisions.